2017
DOI: 10.1016/j.jnutbio.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs and sulforaphane: a target for chemoprevention and suppression of prostate cancer

Abstract: Long non-coding RNAs (lncRNAs) have emerged as important in cancer development and progression. The impact of diet on lncRNA expression is largely unknown. Sulforaphane (SFN), obtained from vegetables like broccoli, can prevent and suppress cancer formation. Here we tested the hypothesis that SFN attenuates the expression of cancer-associated lncRNAs. We analyzed whole genome RNA-sequencing data of normal human prostate epithelial cells and prostate cancer cells treated with 15 μM SFN or DMSO. SFN significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…Additionally, enforced LINC01116 expression significantly increased tumorigenicity. These findings provide evidence that LINC01116 functions as a key mediator of cell cycle, proliferation, migration, invasion, tumorigenesis and angiogenesis, and thus represents a promising target for glioma treatment, while LINC01116 has just been reported to regulate the proliferation of prostate cancer cells in 2017 …”
Section: Discussionmentioning
confidence: 83%
“…Additionally, enforced LINC01116 expression significantly increased tumorigenicity. These findings provide evidence that LINC01116 functions as a key mediator of cell cycle, proliferation, migration, invasion, tumorigenesis and angiogenesis, and thus represents a promising target for glioma treatment, while LINC01116 has just been reported to regulate the proliferation of prostate cancer cells in 2017 …”
Section: Discussionmentioning
confidence: 83%
“…Numerous studies in recent years have shown a significant correlation between lncRNAs and tumor development and progression, 17,18 and identification of novel lncRNA-based prognostic and therapeutic targets is currently a fervent topic in cancer research. 21 OSCC and NPC are the two main types of HNSCC, 22 and LINC01116 was dramatically upregulated in both types compared with the adjacent normal tissues. The microarray results were successfully F I G U R E 2 The expression level and prognostic significance of the identified lncRNAs in HNSCC.…”
Section: Discussionmentioning
confidence: 95%
“…To determine the biological significance of the aberrantly expressed lncRNAs in HNSCC, we analyzed two microarray datasets-GSE30784 and GSE29330from the GEO database and identified 21 overlapping lncRNAs, of which six were upregulated and 15 were downregulated. [19][20][21] To further dissect the underlying mechanism of the oncogenic role of LINC01116 in HNSCC, we mapped the functional networks of lncRNAs using circlncRNAnet, an integrated web-based resource, to screen for the coexpressing genes of LINC01116. Three overlapping upregulated lncRNAs and three overlapping downregulated lncRNAs were randomly selected to verify the integrated analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…Primers used are as follows: AC145124.1, Forward-5′ -GGCTAACGTAGGCACTCTCG-3′, Reverse-5′-CACTTCTTCCACGAGCACCT-3′; AC010168.2, Forward-5′-TTGGTGTGCAGTTTGGTGTA-3′, Reverse-5′-TAAGTGGTCTGCCCATGTTT-3′; MIR200CHG, Forward-5′-CTGACCAACAACCTCTGACCTTCA-3′, Reverse-5′-AGGCAGCCATTTTGTCTCCTTC-3′; AC098613.1, Forward-5′-CAGGGAGGAAGGTATGTGGT-3′, Reverse-5′-ATCATGTAGGTGCAGGCAGA-3'; HIST4H4, Forward-5'-ATGTGGTGTACGCGCTGAAA-3', Reverse-5′-CGCCAAGTCTAATCCCGAGC-3′; GAPDH, Forward-5′-CTCCAAAATCAAGTGGGGCG-3′, Reverse-5′-TGGTTCACACCCATGACGAA-3′. Relative expression was determined by using the formula: Relative expression = 2 -(Cq gene -Cq GAPDH ) [40,41]. Analysis of the correlation between AC010168.2 and HIST4H4 expression was performed using SPSS 22.0 software.…”
Section: Blca Tissuementioning
confidence: 99%